Analisa Penyelesaian Perbatasan Laut Antara Peru dengan Chili yang Diselesaikan Oleh Mahkamah Internasional (ICJ) - Sholikah, Dwi Imroatus (Jurnal Hukum Lex Generalis, 2020)
The law of the sea, which is a branch of international law, has developed a long time ago and has undergone very significant changes in its regulations. Moreover, the law of the sea plays a very important role in limiting the areas of the sea, land, and waters of a country. Which here the sea is a road that is very often used to connect one country to another for trade purposes and even for other interests. On the other hand, there is international maritime law to protect natural resources from being misused. The International Court of Justice is to resolve disputes between member countries. This institution also provides opinions or advice to official bodies and specialized agencies established by the United Nations. In carrying out its duties, the International Court of Justice refers to international conventions to determine cases recognized by countries in dispute. The ICJ is also guided by international customs which are evidence of common practice.